THE TERMINOLOGY USED TO DESCRIBE TEAMWORK IN THE HEALTH CARE SYSTEM - Ivanović, Sunčica (Acta medicae Medianae, 2021)
Introduction:Teamwork in the healthcare system is a necessity because of the complexity of health problems and the emancipation of users. Teamwork is a gold standard in the healthcare of patients where each member has specific task and function while respecting the others in the team and characterized by working together, goal, purpose, ethics, problem-solving ideas, good communication, shared responsibility and synergy. Aims:to describe characteristics and benefits of teamwork in healthcare, to describe the types of teams in health care, and to identify the main limiting factors for a team’s success in healthcare. Method: literature review. Results and discussion:The effects of teamwork in healthcare are: reducing the length of stay in hospital, reducing costs of healthcare, increasing the satisfaction of users and care givers, improving the quality of health services, efficient use of resources in healthcare, improvement the quality of communication. Unlike the traditional disease focused approach, nowadays, the teams are focused on holistic approach to patient and health-disease phenomenon. Conclusions:When performing complex tasks that involve quick decision-making, rapid interventions and quick solutions, especially in emergencies in healthcare and in treatment of chronic disease, teamwork is invaluable. The main limiting factors for the success of the team in healthcare are: lack of staff in healthcare, insufficiency in competency of staff, limited financial resources, inability of team members to work in team (lack of experience and education), lack of leadership in the healthcare institution for encourage and promote teamwork.